Composition and structure of upper Jurassic black shales from the Moscow region considering new data - S. Yu. Malenkina (Известия высших учебных заведений: Геология и разведка)
For the first time the sections of the southeast of Moscow and adjacent areas of the Moscow region, which contain the Lower Volgian and Oxfordian black shales, were studied in detail and described. The existence there of the autochthonous (not redeposited) Lower Volgian deposits was not recognized until recently and studied shales traditionally were referred to as the Middle Volgian substage in the past. The paper gives a detailed description to the shales of both levels and, for the first time, analytical data showing relatively high contents of the organic carbon like their analogs in the Kostroma region and elevated concentrations, often significant, of a number of elements such as V, P, Ni, Mo, Cr, Cu, Pb, As, S, Fe, Zn. The accumulation of the shales is discovered to depend on a paleorelief and the depth of the pool, and they are confined to the pre-Jurassic structural hollows, while in the shallow elevated areas there are low-thickness condensed sections with the complete absence of the shales and the presence of almost solely phosphate interlayers.